2000
DOI: 10.1034/j.1600-0412.2000.079001043.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is a risk factor for early pregnancy loss after IVF or ICSI

Abstract: Obesity is an independent risk factor for early pregnancy loss. This risk is, in part, related to the lower number of collected oocytes in obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
2
10

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 0 publications
1
86
2
10
Order By: Relevance
“…86 Finally, in recent studies on PCOS women conceiving after in vitro fertilization or intracytoplasmatic sperm injection, it was observed that those with obesity had higher Obesity and the polycystic ovary syndrome A Gambineri et al gonadotrophin requirement during stimulation, 87 fewer oocytes, a higher abortion rate and lower live-birth rate than their non-obese counterpart. 88 In conclusion, a decreased efficiency of the different treatments for ovulation and fertility induction may be expected in obese PCOS women. The presence of hyperinsulinemia is probably the major factor responsible for this undesirable condition.…”
Section: Androgen Abnormalitiesmentioning
confidence: 99%
“…86 Finally, in recent studies on PCOS women conceiving after in vitro fertilization or intracytoplasmatic sperm injection, it was observed that those with obesity had higher Obesity and the polycystic ovary syndrome A Gambineri et al gonadotrophin requirement during stimulation, 87 fewer oocytes, a higher abortion rate and lower live-birth rate than their non-obese counterpart. 88 In conclusion, a decreased efficiency of the different treatments for ovulation and fertility induction may be expected in obese PCOS women. The presence of hyperinsulinemia is probably the major factor responsible for this undesirable condition.…”
Section: Androgen Abnormalitiesmentioning
confidence: 99%
“…Our data suggest that the frequently reported fertility disorders in obese or diabetic women (Pasquali et al, 2003) may be not only due to the toxic effects of NEFA on granulosa cells, which mainly lead to amenorrhea (Mu et al, 2001), but could also originate from direct detrimental effects on the cumulus-oocyte complex. The latter could explain the disappointing IVF or intracytoplasmic sperm injection (ICSI) results, and the higher risk for early pregnancy loss in obese women, as has been documented by Fedorcsak et al (2000 and and Pasquali et al (2003). Ongoing research on humans should confirm or refute the validity of applying this bovine model in human studies.…”
Section: Introductionmentioning
confidence: 99%
“…These alterations may explain impaired ovulatory function and so reproductive health. Because of lower implantation and pregnancy rates, higher miscarriage rates, and increased maternal and fetal complications during pregnancy, obese women have a lower chance to give birth to a healthy newborn (3)(4)(5)(6). In this review, the effects of obesity on fertility and effective management of infertility in obese and overweight women is summarized.…”
mentioning
confidence: 99%